At the end of the expansive society? - Jochum, Georg (2021)
The article argues that the coronavirus-pandemic and other recent epidemics can be interpreted as unintended side effects of the expansive penetration of technical-capitalist civilization into natural areas. The ‚colonizing‘ reconfiguration of the ecological web of life and the reduction in biodiversity increase the risk of viruses being transmitted from animals to humans. A historical review makes it clear that similar processes have accompanied human civilization history and that the colonization of nature has been accelerated since the modern expanding society developed in the 16th century. The associated capitalist-technical appropriation of the web of life is currently experiencing a comprehensive social-ecological crisis. The corona crisis also exemplifies the unsustainability of the modern expanding society and its colonial relationship with nature. In order to avoid the increase in such crises, a social-ecological transformation is necessary, which is connected with the development of a post-colonial relationship with nature and initiates the transition to a sustainable integration- society.